Pengaruh Konten Pemasaran dan Citra Merek Terhadap Minat Beli Somethinc (Studi Kasus pada Pengguna Somethinc di Marketplace Shopee) - Liani, Ade; Ekawaty, Novian (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Effect of Content Marketing and Brand Image on Purchase Intention of Somethinc (Case Study on Somethinc Users in the Shopee Marketplace). Thesis. Faculty of Economics, University of Singaperbangsa Karawang. This study aims to determine, analyze, and explain the effect of Content Marketing and Brand Image on Purchase Intention Somethinc on the Shopee marketplace. The results of the research show that descriptively Content Marketing (X1), Brand Image (X2), and Purchase Intention (Y) are considered good. The results of verification analysis of the variables Content Marketing and Brand Image are stated to influence each other and show a strong level of influence. The partial effect of Content Marketing on Buying Interest is 51,9%, while the partial effect of brand image on buying interest is 30%. The simultaneous effect of Content Marketing and Brand Image on Purchase Intention is 67,6% and the remaining 32,5% is another variables not examined.